Electrostatic complexes between thermosensitive cationic microgels and anionic liposomes: Formation and triggered release of encapsulated enzyme. (October 2019) - Panova, Tatiana V.; Kostenko, Stepan N.; Efimova, Anna A.; Evtushenko, Evgeniy G.; Plamper, Felix; Richtering, Walter; Yaropolov, Alexander I.; Yaroslavov, Alexander A.
Graphical abstract: Highlights: Charged thermosensitive microgels are promising candidates for multi-liposomal conjugate formation. Anionic liposomes sorbed on the thermosensitive microgels release their payload after heating over VPTT. The effectiveness of liposomes payload release is determined by the cross-linking degree. Color reaction of the enzyme with a substrate enable to visually control the liposomes payload release. Abstract: The multi-liposomal conjugate with encapsulated enzyme laccase is described, capable of releasing the payload when changing the temperature. For this, thermosensitive cationic microgels were synthesized, differing in the molar content of cross-linker from 2 to 8 mol%. The microgels collapsed when heated beyond the volume phase transition temperature (VPTT) of 38–40 °C, while the degree of the surface area contraction (φ) decreased with increasing the cross-linker content. At lower temperature, each swollen microgel particle, ca. 320 nm in diameter, adsorbed about 200 intact 50 nm anionic liposomes. Over VPTT, the liposomes disrupted and released their payload that was visually detected via a color "development" of a loaded into liposomes laccase substrate in the surrounding solution: the higher φ, the more released enzyme and the higher colored product concentration. So, the correlation between the microgel cross-linking degree and the amount of released liposome payload was demonstrated for the first time. The results we have obtained are of interest for constructing drug carriers, catalysts and diagnostic systems.